The Academic Profession in Canada - Alison Jefferson (Brock University, 2021)
There is little research on the socialization of doctoral students in Canada. Using data collected as part of the Canadian sample of the Academic Professions in the Knowledge Society project, this paper explores the reported doctoral experience of full-time academic faculty in Canadian universities who were 'successfully' socialized to the role of scholar, to find potential factors affecting doctoral experience and career progression. This paper suggests that financial and faculty support are key to doctoral success. With disciplinary nuance alive and thriving, many contemporary doctoral students may be subject to unfair disadvantages, which may be of the underlying reasons for high attrition from doctoral programs. Results indicate teaching continues to be an overlooked aspect of doctoral training, in favor of research; the associated faculty support which often accompanies research, along with the potential for funding for the research-related activity, may be a significant factor in socialization.